POLYACRYLATE POLYALCOHOL COPOLYMER (VANTRIS®) AS AN OPTION FOR MINIMALLY INVASIVE MANAGEMENT OF VESICOURETERAL REFLUX: OUR EXPERIENCE - Vacic, Nikola; Djordjevic, Ivona; Jovanovic, Zorica; Konstantinović, Strahinja G (Acta medicae Medianae, 2024)
Minimally invasive treatment of vesicoureteral reflux (VUR) has gained popularity in recent decades for numerous advantages of the procedure itself: easy to perform, short inpatient care time compared to open techniques, a rare occurrence of serious complications, and short duration of stay in hospital. There are two groups of injectable tissue augmentation agents: biodegradable and non-biodegradable. Vantris® is a combination of two groups.The aim of the study was to determine the effectiveness of Vantris® as an option in the minimally invasive treatment of VUR. We conducted a prospective study for a period of five years (2015−2019). A total of 24 patients, or 39 renal reflux units (RRJ) were treated with Vantris®. Reflux was unilateral in 9 patients (37.5%), and bilateral in 15 patients (62.5%). Reflux grade was V in two ureters (5.12%), IV in 6 ureters (15.38%), III in 22 (56.42%), II in three (7.69%) and I in 6 (15.38%). Median follow-up was 12 months and included urinalysis, urinary tract ultrasound, and voiding cystoureterography at one year. Reflux was eliminated in 36 ureters (92.31%). Two patients developed ureterovesical junction obstruction, while one patient required another injection treatment. Vantris® can be used to treat VUR successfully and with a low percentage of complications. The application is simple, the rate of complications is reduced to a minimum, and therefore it could become the treatment of choice for the treatment of VUR.
Keywords: vesicoureteral reflux, children, Vantris®